Upaya Meningkatkan Kemampuan Membaca Efektif melalui Metode Skimming dan Scanning pada Siswa Kelas VII SMP Negeri Panca Marga Kolimasang - Agnes Sakan Nini Tukan; Vinsensius Crispinus Lemba; Yoakim Yolanda Mario Leu (Social Science Academic, 2023)
This thesis raises the issue of efforts to improve effective reading skills through skimming and scanning methods for class VII students of SMP Negeri Panca Marga Kolimasang. Reading has several types, including speed reading, silent reading, beautiful reading, language reading and literature reading. Reading speed is a skill that must be trained. Success in mastering and practicing speed reading depends on attitude, level of seriousness, and readiness to practice. However, at school students are not given the opportunity to read so that students are less proficient in speed reading techniques. This study aims to find out and describe whether the use of skimming and scanning methods can improve the effective reading ability of class VII students of SMP Negeri Panca Marga Kolimasang. This type of research is this research is classroom action research (PTK). The implementation of this research consisted of two cycles. each cycle through the stages of planning, implementation, observation, and reflection. The method used is descriptive quantitative. The results of this study indicate that the average reading speed in the pre-cycle is 88 wpm with a total of 6 students who reach the very fast category. The results of students' reading speed after applying the skimming and scanning method in cycle I averaged 129 wpm with 16 students who achieved the very fast category, while in cycle II the average reading speed was 195 kpm with 27 students who achieved the very fast category. Thus it can be concluded that the skimming and scanning method can improve the effective reading skills of class VII students of SMP Negeri Panca Marga Kolimasang.